Synchronous uterine adenocarcinoma and leiomyosarcoma – a case study - Dudzik, Kamila; Krzysteczko, Agnieszka; Kolny, Leon; Bąk, Agnieszka; Stawicka-Ociepka, Ewelina; Nowosielski, Krzysztof (Menopause Review/Przegląd Menopauzalny, 2017)
Synchronous gynecological cancers are rarely described. Those cases account for approximately up to 6% of female genital tract malignancies. The presence of synchronous endometrial adenocarcinoma and gynecological tract neoplasia is rare – the most commonly described is synchronous adenocarcinoma and endometrial ovarian cancer (accounting for 15-20% of ovarian neoplasia and 5% of endometrial cancers). Concomitant uterine carcinosarcoma and ovarian cancer, or endometrial adenocarcinoma are extremely rare. Up till now, only 3 cases of synchronous adenocarcinoma and leiomyosarcoma were described. In the present study a case of 60-year-old woman diagnosed with synchronous endometrial adenocarcinoma and leiomyosarcoma uteri is described. As the preoperative evaluation revealed endometrial adenocarcinoma G2 with intermediate-risk of lymph node metastasis and synchronous leiomyosarcoma G3, total hysterectomy with bilateral salpingo-oophorectomy and systemic lymphadenectomy was performed showing no lymphatic involvement. In the postoperative evaluation the patient was qualified to adenocarcinoma low recurrence-risk group (adenocarcinoma G1 with no LVSI, FIGO IA) – no further radiotherapy was required. However, as synchronous leiomyosarcoma G3 was diagnosed, we decided to refer the patient for adjuvant chemotherapy. Contemporary recommendation on the diagnosis and treatment of uterine carcinomas, especially uterine leiomyosarcomas, is also described in this paper. The presented case showed that diagnosis and treatment of women with uterine tumors should be individualized as in the same case an extremely rare cancer type can be present which, consequently, changes the treatment regimen and prognosis.